(3TQM JSgjd GdahGFO hJcejd GdebGUOs - (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s; (3eMeO Hf YHO Gddg, GHf eGdc GdWGFj GdLqjGfj, CHh YHO Gddg, LeGd GdOjf,J (B672 (3g` s
(3ChdgG (B:s
(3jHOC HHGH GdMGd Hbhdg(B: (3hgh eG Od Ydi gjFI hUGMHgG eJVefkG eG ajg eYfi hMbg GdfUH hbO ojLQ HHGA RGFOI s
(3BNQgG (B:s
(3hbO jLGH Ohf bSe eQGO, ceG jLGH HCNhGJgG adG CYde GSJYeGdgG ced HMeO Gddg jJdhg aj GdQGHY HGH GdEVGaI s
(3hgj eYGQVIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B223 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B130s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B359 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B521 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B166 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B405s
Keywords: (3GdfMhs